PENGARUH PROFITABILITAS, CAPITAL INTENSITY DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA P ERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PADA TAHUN 2018-2020 - Ramadhan Putra Nanda; Halim Herman Edyanus; Haryetti Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the effect of profitability, capital intensity, and leverageon earnings management. The population in this study includes manufacturingcompanies in the industrial sector and consumer goods listed on the IndonesiaStock Exchange (IDX) in 2018-2020 as many as 51 companies. The samplingtechnique used was purposive sampling method with the number of samples thatmet the criteria as many as 27 companies. Statistical Program for Social Science(SPSS) is used as a method to analyze the data that has been obtained. The resultsshowed that profitability, capital intensity and leverage had a significant positiveeffect on earnings management Keywords: Profitability, Capital Intensity, Leverage, Earnings Management